Interreligious Tolerance In Higher Education: A Study Of Islamic Campus In Central Kalimantan - Muhammad Redha Anshari; Hamdanah Hamdanah; Endah Mustika Pertiwi; Linda Wirda Sari (Institut Agama Islam An-Nawawi Purworejo, 2022)
The diversity of the Indonesian nation also extends to the realm of religious differences. This causes Indonesia to be very vulnerable to friction, so there is a need for guidance regarding tolerance to prevent this condition. Central Kalimantan, which is synonymous with being a tolerant religious area, through universities provides guidance to students regarding tolerance. This research is (field research) in the form of qualitative descriptive, with data collection techniques namely, observation, interviews, and documentation. Based on the results of the research conducted, it was found that, 1) the aim of fostering tolerance I PAI STAI Kapuas and PAI FTIK IAIN Palangka Raya is to equip students with a more moderate outlook and behavior in understanding religion and prioritizing tolerance, 2) the coaching method used is the advice method , and lecture or discussion methods, 3) the pattern of use uses a democratic approach because students act as partners.